2008
DOI: 10.1115/1.2842246
|View full text |Cite
|
Sign up to set email alerts
|

A Full-System Approach of the Elastohydrodynamic Line/Point Contact Problem

Abstract: The solution of the elastohydrodynamic lubrication (EHL) problem involves the simultaneous resolution of the hydrodynamic (Reynolds equation) and elastic problems (elastic deformation of the contacting surfaces). Up to now, most of the numerical works dealing with the modeling of the isothermal EHL problem were based on a weak coupling resolution of the Reynolds and elasticity equations (semi-system approach). The latter were solved separately using iterative schemes and a finite difference discretization. Ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
111
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 13 publications
0
111
0
4
Order By: Relevance
“…Note that the equivalent elastic surface contains the total elastic properties of the original contact surfaces, and hence the solution will define the total elastic deformation of both contacting surfaces [2,21].…”
Section: Mathematical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…Note that the equivalent elastic surface contains the total elastic properties of the original contact surfaces, and hence the solution will define the total elastic deformation of both contacting surfaces [2,21].…”
Section: Mathematical Modelmentioning
confidence: 99%
“…where H 0 is a central offset film thickness and D is the elastic deformation [1,21] (see Section 2.2).…”
Section: Film Thickness Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…The temperature increase in the lubricant film would reduce the viscosity and thereby reduce the coefficient of friction. In a more recent study [6], the present authors used a more advanced and thoroughly validated [5,[20][21][22] 3D numerical model to predict the effect of thin insulating layers on full film elastohydrodynamic (EHD) friction to be compared with experimental measurements. The presented simulations, validated by experiments, showed that applying a thin diamond-like carbon coating to metal surfaces creates an insulating effect that, due to the increased liquid lubricant film temperature at the center of the contact, locally reduces lubricant viscosity and thus friction.…”
Section: Introductionmentioning
confidence: 99%